Fabrication and Mechanical Properties of Chitosan/FHA Scaffolds - Majid Salehi; Sahar Molzemi (Advances in Polymer Technology)
Fluor-hydroxyapatite (FHA) is a biomaterial with dental and orthopedic potential that is highly regarded as a result of bioactivity and high biocompatibility. Chitosan is used as a growth promoting agent in the tissues of the tooth and bone. Composite scaffold from these biomaterials is used as a pattern of natural bone and tooth grafts in tissue engineering. In this study FHA was synthesized through coprecipitation method. Then chitosan/FHA composites with different amounts of FHA (15 and 30 wt%) were prepared via freeze drying way. Structural and physical characteristics of the scaffolds were determined by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) spectra, and morphological properties of the scaffolds were investigated using SEM evaluation. The compressive strength, water-uptake capacity, and biodegradation behavior of scaffolds were performed, as well. The results indicated that chitosan/30%FHA scaffold showed more compressive strength, lower biodegradation in phosphate buffer solution after 4 weeks. Therefore, it might be a suitable scaffold for tooth engineering.